Influence of nutrients and pH on the efficiency of vertical flow constructed wetlands treating winery wastewater. (August 2021) - Sánchez, M.; Gonzalo, O.G.; Yáñez, S.; Ruiz, I.; Soto, M.
Graphical abstract: Highlights: VF CWs reached 88–98 %COD and 59–93 % TN removals at 110−170 g COD/m 2 ·d. Nutrient shortage and low pH do not affect the removal efficiency of COD and BOD5. Low influent pH strongly impairs nitrification and partially denitrification. New strategies for the separate or combined effluent treatment in wineries arise. Abstract: Winery wastewater is characterized by high organic content, low nutrient content and low pH at least during vintage periods. The effect of nutrient shortage and low pH on constructed wetlands (CWs) operation was scarcely studied, but early field studies indicate that some operational problems can arise. This work aims to determine the effect of nutrient shortage and acidic pH during the treatment of high organic load wastewater in one-step vertical subsurface flow (VF) CWs. Two lab scale VF units at hydraulic loading rates over 70 L/m 2 ·d and surface loading rate in the range of 110−170 g COD/m 2 ·d were operated for periods with and without nutrients in the influent as well as with influent pH of 7.0 and 4.5. The results showed that neither low nutrient nor low pH impair organic matter removal whilst low pH decreased nitrogen removal rates. At low pH, the effluent concentration of ammonia and nitrate increased, indicating deterioration in both nitrification and denitrification processes. The paper discuss the implications of these findings for a better strategy in the treatment of winery process wastewater, such as options for separate treatment or its combination with other nutrient-containing streams.